Cyber physical systems : model-based design : 8th International Workshop, CyPhy 2018, and 14th International Workshop, WESE 2018, Turin, Italy, October 4-5, 2018, Revised Selected Papers /: model-based design : 8th International Workshop, CyPhy 2018, and 14th International Workshop, WESE 2018, Turin, Italy, October 4-5, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available